2015
DOI: 10.3402/ejpt.v6.28306
|View full text |Cite
|
Sign up to set email alerts
|

How to quantify exposure to traumatic stress? Reliability and predictive validity of measures for cumulative trauma exposure in a post-conflict population

Abstract: BackgroundWhile studies with survivors of single traumatic experiences highlight individual response variation following trauma, research from conflict regions shows that almost everyone develops posttraumatic stress disorder (PTSD) if trauma exposure reaches extreme levels. Therefore, evaluating the effects of cumulative trauma exposure is of utmost importance in studies investigating risk factors for PTSD. Yet, little research has been devoted to evaluate how this important environmental risk factor can be b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
96
1
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 115 publications
(118 citation statements)
references
References 46 publications
17
96
1
4
Order By: Relevance
“…Kessler et al, 2017, 1995; Smith, Summers, Dillon, & Cougle, 2016). Besides the type of trauma, numerous studies have found that cumulative trauma, mostly defined as the number of different trauma types, is associated with greater PTSD risk and symptom severity (Green et al, 2000; Karam et al, 2014; Wilker et al, 2015). Simpson, Comtois, Moore, and Kaysen (2011) found that the prevalence of PTSD increased from 53.7% to 67.2% when patients were asked to rate their symptoms for their complete trauma history instead of for only their worst event.…”
Section: Introductionmentioning
confidence: 99%
“…Kessler et al, 2017, 1995; Smith, Summers, Dillon, & Cougle, 2016). Besides the type of trauma, numerous studies have found that cumulative trauma, mostly defined as the number of different trauma types, is associated with greater PTSD risk and symptom severity (Green et al, 2000; Karam et al, 2014; Wilker et al, 2015). Simpson, Comtois, Moore, and Kaysen (2011) found that the prevalence of PTSD increased from 53.7% to 67.2% when patients were asked to rate their symptoms for their complete trauma history instead of for only their worst event.…”
Section: Introductionmentioning
confidence: 99%
“…the trauma, depends upon several factors. These include the type, proximity and frequency of traumata and previous experiences as well as the genetics, epigenetics, resilience, gender, age or cognitive capacity of the individual who encounters trauma [1][2][3][4][5].Given this variation, it is surprising that merely counting traumatic exposures can predict detrimental consequences for psychological functioning. This was, however, shown in the seminal Adverse Childhood Experiences (ACE) studies, and now Scheidell and colleagues demonstrate that it also occurs for substance use and abuse [6].…”
mentioning
confidence: 99%
“…the trauma, depends upon several factors. These include the type, proximity and frequency of traumata and previous experiences as well as the genetics, epigenetics, resilience, gender, age or cognitive capacity of the individual who encounters trauma [1][2][3][4][5].…”
mentioning
confidence: 99%
“…Wie in zahlreichen Forschungsarbeiten gezeigt werden konnte, erhöht das mehrfache Erleben verschiedenartiger traumatischer Ereignisse das Risiko, eine posttraumatische Belastungsstö-rung (PTBS) zu entwickeln [5,19,26,41]. Mit jedem erneuten Erleben eines traumatischen Stressors steigt die Wahrscheinlichkeit einer Traumafolgestörung, ein Effekt, der in der Literatur als Bausteineffekt beschrieben wurde [36].…”
Section: Die Zentrale Rolle Der Psychischen Gesundheitunclassified